Multikulturalisme Islam Dalam Kebijakan Pemerintah Terhadap Orientasi Pesantren di Indonesia - Istiani, Nurul (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
This qualitative study with a normative-philosophical approach intends to identify and explore multicultural Islamic values contained in the orientation of Pesantren implementation in Indonesia. The primary data of this study uses the document text of Law No.18 of 2019 concerning Pesantren. Various multicultural Islamic values conceptualized by Azyumardi Azra are used as the basis for perspective in the analysis of the subject matter of this study. The study data was collected through documentation techniques. Meanwhile, data analysis includes the stages of reduction, presentation, and verification. This study concludes that there is a content of multicultural Islamic values in the policies of the Government of Indonesia related to the orientation of the implementation of Islamic boarding schools, including the value of humanism in the orientation of personal formation of Muslims who value religion and humanity. Then, the value of tasamuh, and wasatiyyah in the orientation of the personal formation of Muslims who maintain religious harmony. Furthermore, the value of peace in the personal formation of Muslims that maintain the integration of the nation and state. The theoretical implications of this study affirm that multicultural Islamic values can be disseminated in the regulation of laws and regulations in Indonesia. Limitations have not yet been This study has not identified various forms of obstacles or challenges in the implementation of the Pesantren Law in Indonesia.